More Gray, More Volatile? : Aging and (Optimal) Monetary Policy - Baksa, Daniel (IMF Working Papers; Working Paper ;, 2019)
The evidence on the inflation impact of aging is mixed, and there is no evidence regarding the volatility of inflation. Based on advanced economies' data and a DSGE-OLG model, we find that aging leads to downward pressure on inflation and higher inflation volatility. Our paper is also the first, using this framework, to discuss how aging affects the transmission channels of monetary policy. We are also the first to examine aging and optimal central bank policies. As aging redistributes wealth among generations and the labor force becomes more scarce, our model suggests that aging makes monetary policy less effective and in more gray societies central banks should react more strongly to nominal variables.